POLA PEMBELAJARAN PAI UNTUK MENGEMBANGKAN KEPRIBADIAN ANAK DI SEKOLAH DASAR - Trimansyah, Trimansyah (FASHLUNA, 2023)
This research was conducted to determine the learning pattern of Islamic Religious Education in developing children's personalities. The approach used in this study is a descriptive qualitative approach which is the focal point of the learning process used to instill Islamic religious values ​​in children by using various patterns in learning. The research data was collected by means of observation, interviews and documentation and techniques were carried out in the opinion of Miles and Huberman namely, collecting, reducing, displaying and drawing conclusions from existing data. The results of this study are that the PAI learning pattern is more about planting or learning related to worship as a value of the Islamic religion including being taught, praying, being taught morals, being taught about zakat, and also being taught about various good attitudes such as being honest, being polite, discipline, mutual respect, respect, and taught to stay away from various bad attitudes as well as, stay away from arrogance, betrayal, cheating, liars and so on. Learning patterns are very effective in elementary schools so that through this learning the child's good personality will be seen in his daily life.